2(2x-3)=5x-11

Simple and best practice solution for 2(2x-3)=5x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x-3)=5x-11 equation:


Simplifying
2(2x + -3) = 5x + -11

Reorder the terms:
2(-3 + 2x) = 5x + -11
(-3 * 2 + 2x * 2) = 5x + -11
(-6 + 4x) = 5x + -11

Reorder the terms:
-6 + 4x = -11 + 5x

Solving
-6 + 4x = -11 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-6 + 4x + -5x = -11 + 5x + -5x

Combine like terms: 4x + -5x = -1x
-6 + -1x = -11 + 5x + -5x

Combine like terms: 5x + -5x = 0
-6 + -1x = -11 + 0
-6 + -1x = -11

Add '6' to each side of the equation.
-6 + 6 + -1x = -11 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = -11 + 6
-1x = -11 + 6

Combine like terms: -11 + 6 = -5
-1x = -5

Divide each side by '-1'.
x = 5

Simplifying
x = 5

See similar equations:

| -5x^2+250x-130000=5000 | | (x^2)-19x+9.5=0 | | (x+18)=688 | | 0.4(x+7)-0.1(3x+6)=-0.8 | | 17+20-3=17y | | y=6xt+5xt^2+6 | | 15d+3.2=92 | | 3(5-3)=2(3-1) | | 2+3/5x=9 | | 4(8-2x)=-6x+4(x-4) | | 10=5-12z | | 27*n= | | 0.5x+0.2(9-x)=3.6 | | X+(x+10)+(x+15)=180 | | 3w+2(5w-3)-92=p | | 5+2/3x=9 | | -24z+10=-5 | | 4y=3x-23 | | 5y=-7x-3 | | 6+0.4x=30 | | 0=8x^2-10x-105 | | 25(x+15)+25=65 | | 31+15-10=4x | | X=4y+13 | | X+x+x+x+x=x+x+10+10+7 | | 3(1-x)+4(x-5)=10 | | 8.1=0.9 | | 4(2k+7)=12 | | 8+3t=100 | | 5+3x=4+5x | | 13(4x-2)-2=50 | | 7+4x=34 |

Equations solver categories